First-principles study of structural, mechanical, thermal, electronic and magnetic properties of highly spin-polarized quaternary Heusler alloy CoYVSn. (February 2021) - Shakil, M.; Sadia, Halima; Zeba, I.; Gillani, S.S.A.; Ahmad, Shabbir; Zafar, M.
Abstract: In this study, a quaternary Heusler alloy (QHA) CoYVSn investigated employing density functional theory (DFT) taking into account exchange potential perdew-burke-ernzerhof (PBE) and generalized gradient approximation (GGA). Structural properties revealed that among three different Wyckoff positions, Type I symmetry is found the most stable. Moreover, the ferro-magnetic (FM), non-magnetic (NM) and anti-ferromagnetic (AFM) phases are also considered, and FM phase is found to be the most stable. The structural, elastic, thermal, electronic, and magnetic characteristics are investigated at optimized lattice parameters 6.6151 Å. Electronic properties further investigated using GGA-mBJ functional, results showed that the considered QHA is a SGS. Calculated formation energy (E f ) for FM phase suggested that the alloy is stable thermodynamically and experimental realization is possible. Magnetic moment estimated using Slater-Pauling rule; Mtot = (Nv –18) μB . The determined elastic properties proved that the alloy fulfills the stability criteria. Debye temperature ( θ D ) 349  K and melting temperature ( T m ) 1228 ± 300  K revealed that the alloy is thermally stable. Also, the calculated high Curie temperature (Tc ) 981  K suggests its suitability for spintronics applications. Highlights: Calculations of structural, mechanical, thermal, electronic and magnetic properties. A spin gapless quaternary Heusler alloy. High Curie temperature. Reliable material candidates for applications in ultra-fast and ultra-low-power spintronics devices.